Check payment system - Barcena, Emmanuel E. (Makati City, Philippines : Bankers Association of the Philippines, 2014)
The Banker's Association of the Philippines has long considered banking education as an activity important not only to ensure the growth and continued strength of its member banks and of the banking industry, but also as a critical element in Philippine socio-economic development.
Background Information -- The Check Payment System -- The Evolution of Check Payment System -- The Benefits of Check Payments -- Risks in Check as Medium Payments -- Non-Check Payment Systems -- The Philippine Clearing House Corporation -- Introduction to MICR and ECCS -- Understanding Details of a check -- The Clearing cycle -- The Future of Check Payment system.
Keywords: CHECK COLLECTION SYSTEM